First ptychographic X‐ray computed tomography experiment on the NanoMAX beamline. Issue 6 (13th October 2020) - Kahnt, Maik; Sala, Simone; Johansson, Ulf; Björling, Alexander; Jiang, Zhimin; Kalbfleisch, Sebastian; Lenrick, Filip; Pikul, James H.; Thånell, Karina
Abstract : Documentation is presented for the first ptychographic X‐ray computed tomography experiment on the NanoMAX beamline, along with a quantitative analysis of the reconstruction quality and a discussion of possibilities for future improvements. Abstract : Ptychographic X‐ray computed tomography is a quantitative three‐dimensional imaging technique offered to users of multiple synchrotron radiation sources. Its dependence on the coherent fraction of the available X‐ray beam makes it perfectly suited to diffraction‐limited storage rings. Although MAX IV is the first, and so far only, operating fourth‐generation synchrotron light source, none of its experimental stations is currently set up to offer this technique to its users. The first ptychographic X‐ray computed tomography experiment has therefore been performed on the NanoMAX beamline. From the results, information was gained about the current limitations of the experimental setup and where attention should be focused for improvement. The extracted parameters in terms of scanning speed, size of the imaged volume and achieved resolutions should provide a baseline for future users designing nano‐tomography experiments on the NanoMAX beamline.